The Level of Female Student Adversity Quotient in Term of Ethnic Background - Firman Antoni; Afrizal Sano (Jurnal Neo Konseling, 2021)
Every student has a goal to be succesfull in everyday activities both in class and outside of lectures. To achieve this success requires fighting power and readiness to face the problem, namely the adversity quotient. This research is motivated by the problem that occur among female students in terms of ethnic backgorunds, namely Javenese and Minangk in overcoming difficulties and problem both inside and outside academia. This type of research is a quantitative descriptive study that describes the Javanese and Minang ethnicities. The sample consisted of 200 people who were divided into two ethnicities with 100 students each who were taken using insidental sampling techniques. The isntrument used was a questionnaire with a Likerd scale model and proessed through statictical techniques with a percentage formula. To see the difference in the level of adversity quotient among female students from javanese and Minang, the t-test technque was used with the help of SPSS 25.0 software. The finding of the study were that there was no significant difference between the level of adversity quotient between female students of Javanese and Minang ethnicities, indicated by significance of 0,039, it was found that the t count was 1,366 which was smaller than the t table of 1,984 with 98 degress of freedom (df) at the 5% confidence level.